Perbandingan Mitos Sejarah di Berbagai Komunitas Lokal: Studi Kasus tentang Perbedaan dan Persamaan dalam Tradisi Lisan - kiswanto koswanto; Nurul Huda (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2023)
Historical myths constitute a crucial element of oral traditions that function in shaping identity, transmitting values, and maintaining collective memory within local communities. Although they are not intended as factual historical records, historical myths play a strategic role in shaping how societies interpret the past and legitimize social and cultural orders. This article aims to compare historical myths across different local communities by examining similarities and differences in narrative structures, social functions, and symbolic meanings embedded in oral traditions. The study employs a qualitative approach with a comparative design, using systematic literature review and content analysis of ethnographic sources, oral history studies, and cultural research. The findings indicate that historical myths share common functions as instruments of collective identity formation, cultural value transmission, and social legitimation. However, notable differences appear in narrative emphasis and symbolic representation, which are influenced by geographical conditions, social structures, and historical experiences of each community. These results demonstrate that historical myths are dynamic and context-dependent, functioning not only as representations of the past but also as active mechanisms in shaping historical understanding and cultural identity in contemporary local societies.